Assessment of local and regional strategies to control bacteria levels at beaches with consideration of impacts from climate change. (January 2019) - Barreras, Henry; Kelly, Elizabeth A.; Kumar, Naresh; Solo-Gabriele, Helena M.
Abstract: The objective of this study was to evaluate relationships between local factors (beach geomorphology and management) and regional factors (infrastructure improvements and temperature changes) against levels of fecal indicator bacteria (FIB) at recreational beaches. Data were evaluated for 17 beaches located in Monroe County, Florida (Florida Keys), USA, including an assessment of sanitary infrastructure improvements using equivalent dwelling unit (EDU) connections. Results show that elevated FIB levels were associated with beach geomorphologies characterized by impeded flow and by beaches with lax management policies. The decrease in EDUs not connected coincided with a decrease in the fraction of days when bacteria levels were out of compliance. Multivariate factor analysis also identified beach management practices (presence of homeless and concession stands) as being associated with elevated FIB. Overall, results suggest that communities can utilize beach management strategies and infrastructure improvements to overcome the negative water quality impacts anticipated with climate change. Graphical abstract: Unlabelled Image Highlights: FIB was observed to decrease over time coinciding with a decrease in EDUs not connected. Manmade structure protected beaches had higher FIB percent exceedances relative to bay and back-reef beaches. Beach management practices are associated with FIB percent exceedances. FIB levels increase with increasing temperatures in the range of 15 to 29 °C. Beach management strategies and infrastructure improvements can counteract the water quality impacts from climate change.